Online Learning of Diversity Theme in 4th Grade During The COVID-19 Pandemic - Rachmalia Fitriani Saleh; Anugrah Ramadhan Firdaus (IKIP Siliwangi, 2022)
This research is motivated by the change in the learning process from face-to-face in class to online learning due to the covid-19 pandemic. This study aims to obtain an overview of the implementation of online learning and the difficulties faced by teachers and students as well as the teaching materials used during online learning. The research method used in this research is descriptive qualitative method. In this research, the subjects of the research were teachers and 4th grade students from two schools. A sample of six students was taken from each school. The instrument used in this research was the interview sheet for teachers and students. Data analysis was done qualitatively, taken from the results of interviews. Based on the research, it was found that the teachers had made learning scenarios in such a way that students could still learn effectively. The main difficulties faced by teachers and students are due to the limited internet that students have with a percentage of 91.7% and the lack of interaction between teachers and students which causes less effective online learning. For teaching materials, the teacher has made their own teaching materials so that students can better understand the material being taught.